Space in the Trinity and in Pastoral Care - Pembroke, Neil (Journal of pastoral care & counseling, 2011)
A central feature of the life of the Trinity is contrast without conflict: God is three and God is one. This dynamic has a spatial reference. The Three draw close to each other in the intimacy of love, but they also give each other space to be. This dynamic is a necessary condition for mature relationships on the human level. It is argued that effective pastoral counseling involves both moving in close through empathy and acceptance, and creating appropriate distance through a process that Martin Buber refers to as confirmation. Confirmation involves wrestling with the other person to help her or him actualize her or his God-given moral and spiritual potential.